Visions From Europe, Photo Exhibition - Panayides, Angelos (My University, 2026)
Palazzo Viceconte, Museo della Fotografia Pino Settanni,Matera, Italy A photographic tribute to Matera Basilicata 2019 by Students and Teachers from 28 Countries Matera European Photography and Matera Diffusa, together with Canon Europe, organized the project Matera European Photography / Visions from Europe, an international event that united the iconographical knowledge and distribution of our places, an original and contemporary vision of Matera and Basilicata.